2022
DOI: 10.31482/mmsl.2022.020
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Metformin in Thyroid Cancer

Abstract: Thyroid cancer is a rare type of malignancy. However, thyroid cancer constitutes more than 90 % of endocrine tumors. Metformin (N', N'-dimethybiguanide) is the most commonly prescribed drug in the world, and the annual number of prescriptions for this drug exceeds 120 million. Metformin is the first-line oral treatment for patients with type II diabetes. Metformin has recently been investigated for potential anti-cancer activity in patients with thyroid cancer by stimulating the Adenosine Mono-Phosphate-Activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Nitric oxide is an example of ROS. It is produced in the body during normal physiological processes and is flushed out by endogenous antioxidant systems (enzymatic and nonenzymatic) such as glutathione peroxidase, catalase, and vitamins (E and C) (24). ROS cause tissue damage; therefore, in diabetic patients, they reduce the presence of endothelial-derived nitric oxide (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide is an example of ROS. It is produced in the body during normal physiological processes and is flushed out by endogenous antioxidant systems (enzymatic and nonenzymatic) such as glutathione peroxidase, catalase, and vitamins (E and C) (24). ROS cause tissue damage; therefore, in diabetic patients, they reduce the presence of endothelial-derived nitric oxide (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab treatment (an anti-TNF-α monoclonal antibody) significantly decreased levels of serum resistin in patients with RA (42). Similarly, it has been demonstrated that oleic acid lowers the expression of the resistin gene in isolated adipocytes (43,44). Therefore, therapy aimed at reducing resistin levels in the blood is one way to make use of our developed understanding of the effect of resistin on the onset of RA.…”
Section: Therapeutic Targetingmentioning
confidence: 99%